VC5509A based fingerprint identification preprocessing system - Jiao Ruili; Fan Jing (2008 9th International Conference on Signal Processing, 2008)
Automated fingerprint Identification is a method to identify a person based on his fingerprint physiological characteristics. Along with the rapid development of fingerprint identification technique and its broad applications, preprocessing algorithm is becoming a significant subject. In this paper, we present an automatic fingerprint acquisition and preprocessing system with a fixed point DSP, TMS320VC5509A and a fingerprint sensor, MBF200. The system is diminutive and flexible. We study preprocessing algorithms including filtering, enhancement, binarization, and thinning. By comparing different algorithms, a best one is selected. The system is implemented with C on the C55X platform.